Wrist fusion using an induced membrane technique for forearm salvage in a patient with an infected open injury with segmental bone loss: A case report. (December 2021) - Chowdhury, James M.Y.; Wilks, Daniel J.; Bhat, Waseem; Vollans, Sam; Foster, Nicholas; Wiper, Jay; Harwood, Paul J.
Abstract: This case report describes the management of a 27-year-old male who, after a quadbike accident, presented with an open, infected, segmental both bone forearm injury with significant bone and soft tissue loss including the radio-carpal joint. Limb salvage was accomplished in the form of a single bone forearm fusion utilising Masquelet's two-stage induced membrane technique to reconstruct the segmental bone defect. The patient proceeded to uneventful bony union by 6 months and returned to driving and riding a quadbike. Despite significant deep infection, successful salvage was achieved using the induced membrane technique. Critical to success was aggressive, repeated debridement alongside restoration of vascular supply and reconstruction of soft tissue defects. We highlight the multidisciplinary approach to management including relevant specialists with a particular interest in limb reconstruction.